Trichoderma–Azotobacter biofilm inoculation improves soil nutrient availability and plant growth in wheat and cotton. (23rd April 2019) - Velmourougane, Kulandaivelu; Prasanna, Radha; Chawla, Gautam; Nain, Lata; Kumar, Arun; Saxena, Anil Kumar
Abstract: Microbial biofilms are gaining importance in agriculture, due to their multifaceted agronomic benefits and resilience to environmental fluctuations. This study focuses on comparing the influence of single inoculation— Azotobacter chroococcum (Az) or Trichoderma viride (Tv) and their biofilm (Tv–Az), on soil and plant metabolic activities in wheat and cotton grown under Phytotron conditions. Tv–Az proved superior to all the other treatments in terms of better colonisation, plant growth attributes and 10–40% enhanced availability of macronutrients and micronutrients in the soil, over control. Confocal and scanning electron microscopy showed that the cells attached to the root tips initially, followed by their proliferation along the surface of the roots. Soil polysaccharides, proteins and dehydrogenase activity showed several fold enhancement in Tv–Az biofilm inoculated samples. Time course studies revealed that the population of Az and Tv in the rhizoplane and rhizosphere was significantly higher with a 0.14–0.31 log colony‐forming unit (CFU) increase in the biofilm‐inoculated treatment in both crops. Enhancement in soil biological activities was facilitated by the improved colonisation of the biofilm, due to the synergistic association between Tv and Az. This demonstrates the utility of Tv–Az biofilm as a multifunctional plant growth promoting and soil fertility enhancing option in agriculture.